Penyuluhan Pentingnya Konsumsi Buah Sayur pada Masa Pandemi Covid-19 di Sdi Al-Azhar 2 - Rosyda Dianah; Muhammad Naufal Rosyidi; Annisa Adhanuraina; Pocut Balqis Muda.C (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Vegetables and fruits are the main sources of vitamins and minerals for the body that are useful for increasing the body's immunity because they contain antioxidants. Some vitamins and minerals that have a role as antioxidants, including vitamin A, vitamin E, vitamin C, selenium, iron, and zinc. These substances are important for increasing the body's immunity during the COVID-19 pandemic as a prevention of the body from virus. The aim of this programme is to give knowledge and awareness about the importance of implementing the General Guidelines for Balanced Nutrition, especially in consuming fruits and vegetables to realize Balanced Nutrition for students in SDI Al Azhar 2. The method used is online counseling with power point materials, displaying videos, providing e-Booklet and filling out pre and post questionnaires. The counseling was attended by 8 teachers and 110 students enthusiastically and filled out the questionnaire completely. The results of this counseling show that the post-test results of the participants have increased in value by 11.75% compared to the results of the pre-test so that it can be concluded that there is a change in the cognitive improvement and enthusiasm of the counselingparticipants. The students also became more enthusiastic about eating vegetables and fruit